The concept of metaphor in the contemporary sculpture (Al-Academy, 2024)
Despite the importance of this term in linguistics and rhetoric ancient and modern literary forms in general, is that it is possible to use in clarifying the foundations of the relationship hidden and manifest between shapes in models art adjacent or successive spatially, as the artwork plastic in general and sculpture in particular consists of formal structure somewhat similar to the structure in any language text and we can decode these blades structure and analyze the implications and come to their meanings and re-read and interpreted under the guidance of the concepts and techniques of neighboring developed primarily for linguistic analysis of texts or launched from their references. This split search to four chapters included the first research problem and its significance, purpose and definition of the terms The second chapter the concept of metaphor in literature and sculpture, and Chapter IV measures search through the analysis of the sample intentionality either Chapter IV has displayed the most important results that arrived search